Synodality in the Reception of the Second Vatican Council and Development of the Pastoral Orientations of the Chilean Bishops’ Conference, 1965–1985 - José Ignacio Fernández (Religions, 2023)
After the Second Vatican Council, the Chilean bishops met in a plenary assembly during May 1968. As a result, the Episcopal Conference of Chile developed its first Pastoral Orientations (POs). Between 1968 and 1985, the Chilean Bishops produced eight different iterations of the POs. The ongoing development of the POs during this period reflected an emerging consensus across the various dioceses of the county. Five aspects of the POs in particular helped develop a synodal culture: (1) to reform the Church, (2) to establish the Church as an evangelizer and servant of humanity, (3) to opt for the base ecclesial communities as the local realization of the People of God, (4), to carry out the liturgical reform and diocesan synods, and (5) to develop intermediate forms of collegiality among the bishops.